Asymptotic distribution of eigenvalues and eigenfunctions of a nonlocal boundary value problem - Sen, Erdogan; Stikonas, Arturas (Mathematical modelling and analysis, 2021)
In this work, we obtain asymptotic formulas for eigenvalues and eigenfunctions of the second order boundary-value problem with a Bitsadze-Samarskii type nonlocal boundary condition. Keywords: differential equation, nonlocal conditions, asymptotics of eigenvalues and eigenfunctions. AMS Subject Classification: 34B24; 34L20; 35R10.